Español - Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1991)
In continuation to the studies of the Genus Sideritis that this Pharmacology Department has done, we have isolated and identificated the flavonoid compounds in the hexanic extracts of ten species of this Genus by an HPLC method. We have to remark the presence of Isoscutellarein-7-0-(allosyl-glucoside), in all the studied extracts.